Acupuncture in Patients with a Vertebral Compression Fracture: A Protocol for a Randomized, Controlled, Pilot Clinical Trial - Hyun-jong Lee; Jung-chul Seo; Sung-hoon Park; Min-ah Kwak; Im hee Shin; Bo-mi Min; Min-su Cho; Woon-seok Roh; Jin-yong Jung (Korean Pharmacopuncture Institute, 2015)
Objectives: A vertebral compression fracture (VCF) is characterized by back pain and fracture of a vertebral body on spinal radiography. VCFs of the thoraco lumbar spine are common in the elderly. In general, appropriate analgesics should be prescribed to reduce pain and, thus, promote early mobilization. The ideal treatment approach for VCFs has not been determined. In Korea, acupuncture and herbal medication have been used to treat VCFs for many years. There is empirical evidence that acupuncture might benefit patients with a VCF. However, no randomized, controlled, clinical trials evaluating the efficacy and the safety of acupuncture for treating a VCF have been published. Therefore, we designed a randomized, controlled, pilot, clinical trial to obtain information for the design of a further full scale trial. Methods: A five week protocol for a randomized, controlled, pilot, clinical trial is presented. Fourteen patients will be recruited and randomly allocated to two groups: a control group receiving interlaminar epidural steroid injections once a week for three weeks, and an experimental group receiving interlaminar epidural steroid injections plus acupuncture treatment (three acupuncture sessions per week for three weeks, nine sessions in total). The primary outcomes will be the pain intensity (visual analogue scale and PainVisionTM system). The secondary outcome measurements will be the answers on the short form McGill pain questionnaire and the oswestry disability index. Assessments will be made at baseline and at one, three, and five weeks. The last assessment (week five) will take place two weeks after treatment cessation. This study will provide both an indication of feasibility and a clinical foundation for a future large scale trial. The outcomes will provide additional resources for incorporating acupuncture into existing treatments, such as nonsteroidal anti-inflammatory medications, narcotics and vertebral augmentation. This article describes the protocol.